Mechanics, Structure and Evolution of Fault Zones 2009
DOI: 10.1007/978-3-0346-0138-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fault Roughness at Various Scales: Implications of Three-Dimensional High Resolution Topography Measurements

Abstract: -Accurate description of the topography of active faults surfaces represents an 23 important geophysical issue because this topography is strongly related to the stress 24 distribution along fault planes, and therefore to processes implicated in earthquake nucleation, 25 propagation, and arrest. 26Up to know, due to technical limitations, studies of natural fault roughness either performed 27 using laboratory or field profilometers, were obtained mainly from 1D profiles. With the 28 recent development of Light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
175
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(181 citation statements)
references
References 44 publications
(73 reference statements)
6
175
0
Order By: Relevance
“…The accuracy of the measurements enables a reliable quantification of the data. Renard et al (2006) and Candela et al (2009) demonstrated precisely the anisotropic self-affine properties of fault topography using ground-based LiDAR and laboratory profilometers. They showed that both slope and intercept are lower in the direction of slip than perpendicular to it.…”
Section: Fault Roughness Scalingmentioning
confidence: 95%
See 3 more Smart Citations
“…The accuracy of the measurements enables a reliable quantification of the data. Renard et al (2006) and Candela et al (2009) demonstrated precisely the anisotropic self-affine properties of fault topography using ground-based LiDAR and laboratory profilometers. They showed that both slope and intercept are lower in the direction of slip than perpendicular to it.…”
Section: Fault Roughness Scalingmentioning
confidence: 95%
“…Representative 2D synthetic self-affine profiles computed with Hurst exponents H jj 0:6 and H ⊥ 0:8. We use a Fourier-based method to simulate both self-affine profiles (Candela et al, 2009). The profile parallel to slip (with the smallest Hurst exponent) appears jagged at small scales and smooth at large scales, compared to the profile normal to slip.…”
Section: Fault Roughness Scalingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we focus on one ubiquitous type of complexity, fault roughness, and explore how deviations from planarity influence the earthquake rupture process. Roughness is observed at all scales using a variety of techniques (laser profilometers from ∼10 μm to ∼10 cm, ground-based LiDAR from ∼0.1 m to ∼100 m, and mapping of surface traces at the largest scales) [1,2,3]. Studies that combined data across the full range of scales suggest that fault surfaces are self-similar.…”
Section: Introductionmentioning
confidence: 99%